2012
DOI: 10.1111/j.1741-3729.2012.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, Working Models of Parenting, and Expectations for Using Television in Childrearing

Abstract: This study used attachment theory to understand college students' working models of parenting and expectations for how they would use television in parenting. We found that secure parent‐child attachment histories were related to more positive expectations of parenting and that avoidant and anxious‐ambivalent parent‐child attachment histories were related to more negative expectations of parenting. Avoidant parent‐child attachment history was related to more positive views about television for children and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 57 publications
(93 reference statements)
1
26
0
2
Order By: Relevance
“…Seven studies found that insecure attachment – particularly avoidance – is related to less desire to have children among non-parents (Nathanson & Manohar, 2012; Rholes et al, 1995, Study 2; Rholes, Simpson, Blakely, Lanigan, & Allen, 1997, Studies 1 and 2; Rholes, Simpson, & Friedman, 2006; Scharf & Mayseless, 2011; Wilson et al, 2007). The link between avoidance and less desire to have children seems to hold for both males and females.…”
Section: Review and Analysis Of The Empirical Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies found that insecure attachment – particularly avoidance – is related to less desire to have children among non-parents (Nathanson & Manohar, 2012; Rholes et al, 1995, Study 2; Rholes, Simpson, Blakely, Lanigan, & Allen, 1997, Studies 1 and 2; Rholes, Simpson, & Friedman, 2006; Scharf & Mayseless, 2011; Wilson et al, 2007). The link between avoidance and less desire to have children seems to hold for both males and females.…”
Section: Review and Analysis Of The Empirical Evidencementioning
confidence: 99%
“…Studies have consistently shown that attachment security is associated with an overall more positive outlook on parenthood – part of what Rholes et al (1997) referred to as “working models of parenthood” (Berant et al, 2001a, 2001b; Mikulincer & Florian, 1998, Study 2; Nathanson & Manohar, 2012; Rholes et al, 1997, Study 1; Vasquez et al, 2002). That is, secure parents perceive parenthood as less threatening and concerning, and secure fathers view parenthood as more rewarding.…”
Section: Review and Analysis Of The Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the research regarding the relationship between attachment and expectations of parenting (Rholes et al, 1997) and attachment and interpersonal relationships (Rholes et al, 2006;Weinfield et al, 1995), the current study examined the relationship between attachment and attitudes of young adults toward interacting with children. Because adults with insecure attachments tend to be less socially competent and confident (Belsky, 1988;Sroufe, 2005) and have more negative interactions with their own children and negative views of themselves as parents (Nathanson & Manohar, 2012;Rholes et al, 1995), we expected that this trend would carry into their interactions with other, nonrelated chil dren. Because of this, we hypothesized that greater attachment security, as measured by respondents having more positive perceptions of parents as sources of security, would predict more positive attitudes toward interacting with children, whereas less attachment security would predict less positive attitudes.…”
Section: The Current Studymentioning
confidence: 99%
“…,眼睛处于脸的中间部位 (Brooks & Hochberg, 1960),大眼 睛 (Sternglanz, Gray, & Murakami, 1977),大瞳孔 (Hildebrandt & Fitzgerald, 1979),又短又窄的嘴巴和鼻子 (Hildebrandt & Fitzgerald, 1979),大而突出的额头 (Alley, 1981)。 婴儿图式特别容易唤起成年个体的反应,让人觉得非常可爱,容易唤起成人个体的照料行为。婴儿 图式可以使人们关注婴儿,对婴儿的需求作出及时的响应,并更愿意花费精力照顾他们 (Brosch, Sander, Pourtois, & Scherer, 2008;Brosch, Sander, & Scherer, 2007) (Power, Hildebrandt, & Fitzgerald, 1982)。由此可见,婴儿 面孔在人类认知加工系统中具有更高的优先等级。 其次,婴儿面孔能有效唤起成人对婴儿的积极情感与态度。婴儿图式越明显的婴儿面孔,其可爱感 越强,越会被评价为更友好、更健康、更具竞争力 (Ritter, Casey, & Langlois, 1991),人们对其养育意愿也 会更强 (Chin, Wade, & French, 2007;Melanie L Glocker et al, 2009a;Volk & Quinsey, 2002) (Gould, 1980;Lorenz, 1971;Tinbergen, 1951)。 而且, 无论是儿童、 性成熟的青少年还是成人, 都一致地对婴儿面孔表现出偏好 (Berman, Cooper, Mansfield, Shields, & Abplanalp, 1975;Fullard & Reiling, 1976;Sanefuji, Ohgami, & Hashiya, 2007) (Bartels & Zeki, 2004;Nitschke et al, 2004;Noriuchi, Kikuchi, & Senoo, 2008 (Cheng, Zhang, Sun, Jia, & Ta, 2015)。 进一步的研究发现,与同样的成人面孔相比,在观看中性和哭泣的婴儿面孔表情时,安全依恋状态可以 显著地正向预测养育动机;具体来说,成人安全依恋状态得分越高,对婴儿面孔的偏好性喜欢更强烈, 并且更愿意再次看相同的婴儿面孔,而且观看时间更长 (Ding, Zhang, & Cheng, 2016)。 通过以上研究表明, 成人依恋影响其对婴儿面孔的偏好反应, 这些研究结论符合 Bowlby (1969这些研究结论符合 Bowlby ( , 1988 对成人依恋行为系统与养育行为系统间关系的看法:这两个系统在个体实施养育行为的过程中会发生交 互作用。与这一观点相一致的是,目前有大量研究发现不安全型的依恋风格会抑制、干扰或消除养育行 为系统的反应 (Feeney, 2002;Mikulincer, Shaver, Gillath, & Nitzberg, 2005);其中具体到养育动机上来说, 安全型依恋风格往往与较强的养育动机有关 (Nathanson & Manohar, 2012;Rholes et al, 1997;Rholes et al, 2006)。因此,研究成人依恋与婴儿面孔偏好的关系可能对深入了解养育行为的本质和成人与婴儿的互动…”
unclassified